The Structure of British Industry / Second Edition - Johnson Peter; Unwin Hyman (1988)
An invaluable source for any student requiring information on the industrial structure, behavior, performance and policy of U.K. industry. Preface, Agriculture, North Sea Oil and Gas, Coal, Steel, Pharmaceuticals, Synthetic Fibres, Information Technology, Motor Vehicles, Food Processing, Constructions, Retailing, Rail Transport, Domestic Air Transport, Insurance, Medical Care, Tourism, Index.